ANALISIS SISTEM PENGENDALIAN INTERN PIUTANG TAK TERTAGIH PADA PT. PLN (PERSERO) UNIT INDUK WILAYAH SULSELRABAR ULP ENREKANG - P, JUMIATI (DECISION : Jurnal Ekonomi dan Bisnis, 2020)
The problem raised in this research is how the procedure for bad debt and how the implementation of the internal control system is bad debt at PT. PLN (Persero) Unit Induk Wilayah Sulselrabar ULP Enrekang. As for the purpose of this study analyze and determine the system of bad debt and the implementation of the internal control system for bad debt PT. PLN (Persero) Unit Induk Wilayah Sulselrabar ULP Enrekang. The research method adopted in this study is descriptive which describes the internal control system of bad debt PT. PLN (Persero) Unit Induk Wilayah Sulselrabar ULP Enrekang. The benefits of this research are scientific benefits and practical benefits. Data collection methods used in this study were observation, and interviews. The results of the study state that the procedure for bad debt in the event that the stages of electricity billing were effective, which were carried out in stages and the implementation of the bad debt internal control system at PT. PLN (Persero) Unit Induk Wilayah Sulselrabar ULP Enrekang has been effective with elements of internal control specifically in the component of its control activities.